Triglyceride-Glucose Index Simulation - S. Mehran Hosseini (Golestan University Of Medical Sciences, 2017)
ABSTRACT Introduction: Since its introduction as a marker of insulin resistance, the triglyceride-glucose (TyG) index has increasingly been used in biomedical literature. However, the TyG index formula seems to be calculated in two different ways, which may consequently produce some confusion regarding the normal cut-offs and cause potential errors in comparing different data. This study tries to explore this discrepancy. Materials and Methods: The TyG index was simulated for different ranges of triglyceride (TG) and fasting blood sugar (FBS). The PubMed and Scopus databases were searched for the TyG index. The results were limited to articles that have mentioned the FBS and TG values. The TyG index was recalculated and compared using the reported FBS and TG values in two different ways. Results: The simulated and reported normal cut-off values for the TyG index in the literature were roughly around 4 and 8. This discrepancy was due to different method of calculating the TyG index, and independent from factors such as age, gender and ethnicity of sampled population. Conclusions: In the TyG index formula, the division sign must be moved out of the square bracket. Otherwise, the normal range must be considered around 8. If the normal value of TyG index is reported as 4, its calculation should be referred to a corrected form of the original formula e.g. ln[FBS(mg/dl) × TG (mg/dl)]/2. KEYWORDS: TyG index, Insulin resistance